Kajian Tempat Perindukan Nyamuk Aedes di Kawasan Kampus Darussalam Banda Aceh - Widya Sari; Tjut Mariam Zanaria; Elita Agustina (Biologi Edukasi: Jurnal Ilmiah Pendidikan Biologi, 2010)
The aim of this research is to determine Aedes mosquitos’ breeding places at Darussalam area including Kopelma village, Tungkob, Limpok, Barabung and Rukoh.  Exploration method and purposive sampling were used in this research, within a hundred of larva sample location and respondents. The data were obtained by larva inventarization and habitat identification. The parameter observe in the research were number of the breeding places. The data were analysed descriptively. The result of this research showed that the breeding places were dominantly found at houses located in the Darussalam village and Limpok. Precisely, Aedes aegypti and Aedes albopictus were found in pure indoor and outdoor containers.